2016
DOI: 10.1177/0269215516640320
|View full text |Cite
|
Sign up to set email alerts
|

A low cost virtual reality system for home based rehabilitation of the arm following stroke: a randomised controlled feasibility trial

Abstract: Objective:To assess the feasibility of conducting a randomised controlled trial of a home-based virtual reality system for rehabilitation of the arm following stroke.Design:Two group feasibility randomised controlled trial of intervention versus usual care.Setting:Patients’ homes.Participants:Patients aged 18 or over, with residual arm dysfunction following stroke and no longer receiving any other intensive rehabilitation.Interventions:Eight weeks’ use of a low cost home-based virtual reality system employing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(150 citation statements)
references
References 21 publications
1
143
0
Order By: Relevance
“…All fifteen studies included were randomized controlled trials [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and were randomized in a blinded manner. Following the appraisal of methodological quality PEDro and Cochrane Collaboration tool, all studies performed well in terms of internal validity (randomization) as well as the results and quality of reporting (e.g., incomplete outcomes, selective outcome reporting and other biases).…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…All fifteen studies included were randomized controlled trials [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and were randomized in a blinded manner. Following the appraisal of methodological quality PEDro and Cochrane Collaboration tool, all studies performed well in terms of internal validity (randomization) as well as the results and quality of reporting (e.g., incomplete outcomes, selective outcome reporting and other biases).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Others three studies used virtual reality rehabilitation programme to improve arm function [29,37] and balance [39]. One study utilized a step training mat, connected wirelessly to the television by a console, to improve balance, stepping, cognition and functional performance in people with Multiple Sclerosis [35].…”
Section: Home-based Intervention Characteristicsmentioning
confidence: 99%
“…Virtual rehabilitation involves both activities carried out 'here and now' and therapy conducted at a distance, called telerehabilitation. A number of reports have been published on this subject, including meta-analyses [14][15][16][17][18][19][20][21][22] evaluating the efficacy of different technical solutions. Standen et al [20] found that VR-based games might also be used at home to help improve motor function in upper limbs after a stroke.…”
Section: Virtual Reality In Rehabilitationmentioning
confidence: 99%
“…A number of reports have been published on this subject, including meta-analyses [14][15][16][17][18][19][20][21][22] evaluating the efficacy of different technical solutions. Standen et al [20] found that VR-based games might also be used at home to help improve motor function in upper limbs after a stroke. Thanks to a variety of tasks, images, and effects that can make conventional motor treatment more engaging, rehabilitation with VR guarantees a greater involvement of the patient and makes them more motivated to exercise regularly.…”
Section: Virtual Reality In Rehabilitationmentioning
confidence: 99%
“…Standen [ 39 ] showed a low-cost virtual reality system for home-based rehabilitation. Participants were assessed at baseline, 4 and 8 weeks using the WMFT and other tests of Daily Living [ 40 ].…”
Section: Wolf Motor Function Testmentioning
confidence: 99%